2020
DOI: 10.1039/d0ra02335c
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption spectroscopy of archetypal chromium porphyrin and corrole derivatives

Abstract: A Cr K-edge XAS study of paradigmatic chromium porphyrin and corrole derivatives has been carried out, providing key data for the Cr(iv) and Cr(v) oxidation states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…(Given their broad importance, there have been surprisingly few XAS and related measurements on porphyrin and corrole derivatives. 20–30 ) The results, interpreted with density functional theory (DFT) calculations, provide detailed insights into the factors influencing the pre-edge shifts of Pt complexes.…”
Section: Introductionmentioning
confidence: 99%
“…(Given their broad importance, there have been surprisingly few XAS and related measurements on porphyrin and corrole derivatives. 20–30 ) The results, interpreted with density functional theory (DFT) calculations, provide detailed insights into the factors influencing the pre-edge shifts of Pt complexes.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain experimental support for the DFT-derived structure, Re L 3 -edge XAS and extended X-ray absorption fine structure (EXAFS) measurements were performed on ReH­[TPC] 2 (several XAS studies of metalloporphyrins and metallocorroles have been reported in recent years ). The Re L 3 -edge absorption of ReH­[TPC] 2 was found to be blue-shifted by 2.5 eV relative to the rhenium foil, as assessed by the first derivatives of the absorption features, consistent with the significantly oxidized state of the metal in the complex (Figure S4).…”
mentioning
confidence: 99%